The prediction of missile trajectories using a Kalman filter: a simulation study. (1st January 2014) - Cho, Byung Rae; Kim, Jaywan
The three-dimensional radar measurements, consisting of range, azimuth, and elevation angle of a flying TBM, help us estimate the theatre ballistic missile (TBM) parameters used in real navy theatre missile defence (NTMD) actions, such as active defence, passive defence, and attack operations. The main purpose of this paper is to optimise the estimation of TBM parameters using the Kalman filter techniques on noise corrupted three-dimensional radar measurement outputs. In this paper, we propose Kalman Filter models to optimally locate TBM positions in a three-dimensional space. More specifically, our proposed models and simulation studies show that we may be able to obtain optimal TBM parameters, such as TBM position, heading, speed, launch position, and destination point and arrival time at the target. The ideas expressed in this paper are those of the authors, and the paper does not represent the views of any agency. Finally, all the references cited in this paper are unclassified documents.